1935
DOI: 10.1017/s0305004100013347
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Structure of

Abstract: The molecular-orbital method has been applied to a study of in its ground state and excited levels, and the relative importance of the perturbation and variational methods has been considered in some detail, as well as the effect of certain integrals which, in discussions of molecular structure, have often been neglected. It appears that the ion should exist in stable equilateral form with a nuclear distance about 0·85 Å., and that all excited levels are unstable.Reasons are given for supposing that the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…This is consistent with a covalently bound trimer in which the unpaired electron resides in an antibonding orbital with a node at one alkali centre but has some spin density on the central atom due to polarization. Such a description is analogous to the molecular orbital picture for H, [22]. The spectra are also consistent with an ionic charge-transfer model corresponding to M~+M-or "M2-M+ , in which the odd electron resides largely on the dialkali cation or anion.…”
Section: Introductionsupporting
confidence: 73%
“…This is consistent with a covalently bound trimer in which the unpaired electron resides in an antibonding orbital with a node at one alkali centre but has some spin density on the central atom due to polarization. Such a description is analogous to the molecular orbital picture for H, [22]. The spectra are also consistent with an ionic charge-transfer model corresponding to M~+M-or "M2-M+ , in which the odd electron resides largely on the dialkali cation or anion.…”
Section: Introductionsupporting
confidence: 73%
“…After its discovery by J.J. Thomson in 1911 [8], the divalent nature of bonding was a mystery to authors of early theoretical papers including illustrious names such as Bohr [9], Massey [10], Hirschfelder [11][12][13][14][15], and Eyring [12,13]. With Lennard-Jones's suggestion, Coulson [16] applied the molecular orbital method to H þ 3 and concluded that its equilibrium structure is an equilateral triangle although the calculation was severely criticized [12]. These pioneering papers were followed by a great many theoretical works especially after the advent of modern computers (see Oka [17], McNab [18] and Anderson [19] for review).…”
Section: Introductionmentioning
confidence: 99%
“…Its exceptional importance in astrophysics related to interstellar media explains the great interest in this ion from astronomy, astrophysics and chemistry communities (for a detailed review, see, [7]). For all these reasons, there have been extensive theoretical and experimental works on this molecular ion since the pioneering (semi-quantitative) work by Coulson [8].…”
Section: Introductionmentioning
confidence: 99%